2007
DOI: 10.1016/j.aorn.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Musculoskeletal Disorders of Perioperative Personnel in the Netherlands

Abstract: Approximately one-third of all cases of sick leave for health care workers are related to musculoskeletal disorders (MSDs) originating in the neck, shoulders, and back. A cross-sectional multicenter survey based on the Nordic Questionnaire for Analysis of Musculoskeletal Symptoms investigated the nature and scope of MSDs among Dutch OR personnel. The three-month prevalence rates for MSDs in OR personnel were found to be high compared to MSDs in the general population and comparable to rates in other strenuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
44
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 8 publications
7
44
0
6
Order By: Relevance
“…Lower back symptoms were the most prevalent problem. This is in accord with the findings of Meijsen et al 30) on the low back pain prevalence in OR nurses that was 58% and the other studies conducted on health care workers 15, 18-20, 22-23, 25, 42) . Bos et al 32) found higher prevalence of the lower back in the OR nurse (76.6%) that could be due to different assignments and variety of tasks.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Lower back symptoms were the most prevalent problem. This is in accord with the findings of Meijsen et al 30) on the low back pain prevalence in OR nurses that was 58% and the other studies conducted on health care workers 15, 18-20, 22-23, 25, 42) . Bos et al 32) found higher prevalence of the lower back in the OR nurse (76.6%) that could be due to different assignments and variety of tasks.…”
Section: Discussionsupporting
confidence: 82%
“…This could be attributable to more prolonged standing posture with the head bent forward. Comparison of the results of this study with the results of the National Health Survey of Iran 43) revealed that the prevalence rates of MSDs in different body regions of the OR nurses studied were significantly higher than those of the general Iranian population, in accordance with the findings of Meijsen et al 30) in the Netherlands, which indicates that OR nurse's job can be considered as a high-risk occupation for developing MSDs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Investigating the impact of each physical demand item showed that awkward body posture, repetitive motions and pressure with hands or wrists are associated with prevalence of LBDs independently. Many studies have shown that perceived physical demands such as polling/pushing heavy objects, moving/lifting/lowering heavy load, performing repetitive motions with hands/wrist and bending or twisting the body were significantly associated with MSDs [28,29,30,31]. The results of the present study are in accordance with the findings of Choobineh, Rajaeefard and Neghab's study which found that high levels of perceived physical demands (scores 10-12 of JCQ) were significantly associated with prevalence of LBDs compared to low-medium levels (scores 0-9 of JCQ).…”
Section: Discussionmentioning
confidence: 99%